Happy People Have Children: Choice and Self-Selection into Parenthood - Sophie Cetre; Andrew E. Clark; Claudia Senik (Institute for the Study of Labor (IZA), 2016)
There is mixed evidence in the existing literature on whether children are associated with greater subjective well-being, with the correlation depending on which countries and populations are considered. We here provide a systematic analysis of this question based on three different datasets: two cross-national and one national panel. We show that the association between children and subjective well-being is positive only in developed countries, and for those who become parents after the age of 30 and who have higher income. We also provide evidence of a positive selection into parenthood, whereby happier individuals are more likely to have children.
Keywords: D1; J13; 330; happiness; fertility; children; income; selection